Recensiones - Hernández, Joaquín; Judex; Achaerandio, Luis; Arias, Carlos; J. M. G. (ECA: Estudios Centroamericanos, 1970)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 25, No. 264, 1970: 512-520.